2001
DOI: 10.4315/0362-028x-64.3.287
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Avian-Specific Probiotic and Salmonella Enteritidis-, Salmonella Typhimurium-, and Salmonella Heidelberg-Specific Antibodies on Cecal Colonization and Organ Invasion of Salmonella Enteritidis in Broilers

Abstract: Salmonella Enteritidis colonizes the intestinal tract of poultry and causes foodborne illness in humans. Reduction of Salmonella Enteritidis colonization in the intestinal tract of poultry reduces potential carcass contamination during slaughter. The purpose of this study was to determine the effect of an avian-specific probiotic combined with Salmonella Enteritidis-, Salmonella Typhimurium-, and Salmonella Heidelberg-specific antibodies on the cecal colonization and organ invasion of Salmonella Enteritidis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
2
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 28 publications
1
34
2
2
Order By: Relevance
“…Concerning the reducing effect of the probiotics on S. Enteritidis shedding rate, the results of Tellez et al, (2001) and Rahimi et al, (2007) in broilers and Fulton et al, (2002) in duckling are parallel with our results.…”
Section: Resultssupporting
confidence: 79%
See 1 more Smart Citation
“…Concerning the reducing effect of the probiotics on S. Enteritidis shedding rate, the results of Tellez et al, (2001) and Rahimi et al, (2007) in broilers and Fulton et al, (2002) in duckling are parallel with our results.…”
Section: Resultssupporting
confidence: 79%
“…Probiotics consist of live or dead organisms and spores (Patterson and Burkholder 2003), non-traditional chemicals (Moore et al, 2006), bacteriophages (Higgins et al, 2005), organic acids (Jarquin et al, 2007;Wolfenden et al, 2007) and others have emerged in the last decades as some of the tools that could be potentially useful in the near future for pathogen control and poultry performance. Probiotics are used now safely to prevent enteric infections especially with S. Enteritidis in newly hatched chicks with successful results (Soerjadi et al, 1981;Fuller 1997;Tellez et al, 2001;Ayed et al, 2004;Wafaa et al, 2006;Higgins et al, 2007a, b;Revolledo et al, 2009). …”
Section: Control Of Smentioning
confidence: 99%
“…In similar case, Murry et al (2006) found lower Coliforms bacteria count in birds by feeding probiotics. Therefore, the beneficial microorganisms establish in the digestive tract and prevent the pathogens (Tellez et al, 2001;La Ragione et al, 2004). Also, in our experiment, Bifidobacterium count was higher at whole period (1 to 42 days).…”
Section: Resultsmentioning
confidence: 48%
“…Estes resultados coincidem com os de outros autores que também não isolaram estes agentes a partir de avestruzes (Ley et al, 2001;Melville et al, 2004). Nos animais jovens investigados nesse estudo, o não isolamento destes micro-organismos pode ser devido à utilização de probióticos no primeiro dia de vida, o que evita a colonização de patógenos, dificultando a sua detecção por métodos tradicionais (Andreatti Filho et al, 2000;Tellez et al, 2001). Redução significativa na excreção de Salmonella Typhimurium foi obtida por Lopes et al, (2007), nos casos de enterites associadas à mortalidade em avestruzes, após administração de bactérias da microbiota entérica de avestruzes para aves recém-nascidas.…”
Section: Resultsunclassified